Stylistics Analysis on Two Famous Lyrical Poems by William Shakespeare and Edmund Waller - Prianto Nofan Muttaqin (English Language in Focus (ELIF), 2022)
This paper discusses stylistics and literary devices in two famous lyrical poems. The poems are titled "Shall I Compare Thee to a Summer Day" by Shakespeare and "Go, Lovely Rose!" created by Edmund Waller. The analysis of these two poems is motivated by a long period of writing. Shakespeare's poetry was written in 1609, while Edmund Waller's was written in 1645. This paper aims to analyze and compare the two famous poems written over a long time. So it can be seen how the development of lyrical poetry during the Renaissance. By using stylistic theory, stylistic elements of language, and literary devices such as rhyme and rhythm for the two poems. Based on this, it is possible to find similarities and differences between the two poems.